Impact of a Booklet about Diabetes Genetic Susceptibility and Its Prevention on Attitudes towards Prevention and Perceived Behavioral Change in Patients with Type 2 Diabetes and Their Offspring. (19th September 2010) - Nishigaki, Masakazu; Sato, Eiko; Ochiai, Ryota; Shibayama, Taiga; Kazuma, Keiko
Abstract : Background . Offspring of type 2 diabetic patients are at a high risk of type 2 diabetes. Information on diabetes genetic susceptibility and prevention should be supplied to the offspring. Methods . A six-page booklet on diabetes genetic susceptibility and prevention was distributed to 173 patients who ere ordered to hand it to their offspring. The patients answered a self-administered questionnaire on booklet delivery and attitudinal and behavioral changes toward diabetes and its prevention in themselves and their offspring. Results . Valid responses were obtained from 130 patients. Forty-nine patients had actually handed the booklet. Booklet induces more relief than anxiety. From the patient's view, favorable attitudinal and/or behavioral changes occurred in more than half of the offspring who were delivered the booklet. Conclusion . The booklet worked effectively on attitudes and behaviors toward diabetes and its prevention both in patients and their offspring. However, the effectiveness of patients as information deliverers was limited.